PENGARUH CURRENT RATIO, DEBT TO TOTAL ASSET RATIO, TOTAL ASSET TURNOVER (TATO), BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO), DAN DANA PIHAK KETIGA (DPK) TERHADAP PROFITABILITAS BANK UMUM SYARIAH - Nahdi, Helmia Mabchut; Jaryono, Jaryono; Najmudin, Najmudin (Faculty of Economics and Business Universitas Jenderal Soedirman, 2013)
The purpose of this research is to analyze the factors that can effect profitability of syariah banking. Variables examined are current ratio, debt to total asset ratio, total asset turnover, operational efficiency and credit, and third party funds . The population in this research is syariah banking. And sample in this research is determined through purposive and unbalance data sampling at period 2005-2011. Total 8 banking companies are taken as study’s sample. The analyze technique used is multiple liniear Regression. The result show that total asset turnover, operational efficiency and credit, third party funds have influence on profitability of syariah banking. While current ratio and debt to total asset ratio haven’t influence on profitability of syariah banking.